B- and T-lymphocyte attenuator stimulation protects against atherosclerosis by regulating follicular B cells. Issue 2 (31st May 2019) - Douna, Hidde; Amersfoort, Jacob; Schaftenaar, Frank H; Kröner, Mara J; Kiss, Máté G; Slütter, Bram; Depuydt, Marie A C; Bernabé Kleijn, Mireia N A; Wezel, Anouk; Smeets, Harm J; Yagita, Hideo; Binder, Christoph J; et al.
Abstract: Aims: The immune system is strongly involved in atherosclerosis and immune regulation generally leads to attenuated atherosclerosis. B- and T-lymphocyte attenuator (BTLA) is a novel co-receptor that negatively regulates the activation of B and T cells; however, there have been no reports of BTLA and its function in atherosclerosis or cardiovascular disease (CVD). We aimed to assess the dominant BTLA expressing leucocyte in CVD patients and to investigate whether BTLA has a functional role in experimental atherosclerosis. Methods and results: We show that BTLA is primarily expressed on B cells in CVD patients and follicular B2 cells in low-density lipoprotein receptor-deficient ( Ldlr −/− ) mice. We treated Ldlr −/− mice that were fed a western-type diet (WTD) with phosphate-buffered saline, an isotype antibody, or an agonistic BTLA antibody (3C10) for 6 weeks. We report here that the agonistic BTLA antibody significantly attenuated atherosclerosis. This was associated with a strong reduction in follicular B2 cells, while regulatory B and T cells were increased. The BTLA antibody showed similar immunomodulating effects in a progression study in which Ldlr − / − mice were fed a WTD for 10 weeks before receiving antibody treatment. Most importantly, BTLA stimulation enhanced collagen content, a feature of stable lesions, in pre-existing lesions. Conclusion: Stimulation of the BTLA pathway in Ldlr − / − mice reduces initial lesion development and increases collagen content of established lesions, presumably by shifting the balance between atherogenic follicular B cells and atheroprotective B cells and directing CD4 + T cells towards regulatory T cells. We provide the first evidence that BTLA is a very promising target for the treatment of atherosclerosis.